PEMANFAATAN DEDAK PADI TERFERMENTASI UNTUK MENINGKATKAN PERTUMBUHAN BABI - I G., MAHARDIKA; SUDIASTRA, I W. (Majalah Ilmiah Peternakan, 2017)
The research has been conducted which aims to analisys the effect of fermented rice bran to pig performance. Completly Randomize Design with 4 treatments and 4 replicates were used in this research. Treatment A: pig given ration containing rice bran without fermentation, treatment B: pig given ration containing 25% fermented rice bran, treatment C: pig given ration containing 50% fermented rice bran, and treatment D: pig given ration containing 100% fermented rice bran. Observed variabels are: feed consumption, average daily gain, feed convertion ratio, digestability of nutrient dan digestible energy (DE). Results of this study concluded the used of fermented rice bran increased of growth and feed efficiency.